The use of an improvised overhead projector to save on chemicals and time - Tan, Merle (Custodio) ([Quezon City s.n.], 1973)
An improvised projector was used in this study to present experiments. The study aimed to encourage teachers to devise simple demonstration experiments which they can use in their science classes and which can save both money and time.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Overhead projection; Chemistry -- Study and teaching